Efforts To Foster Students' Character Through School Literacy Movement At SMK Negeri 1 Tuhemberua - Wita Gustina Zega; Hendrikus Otniel Nasozaro Harefa (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the efforts made to foster student character through the literacy movement and to find out the obstacles faced in fostering character and the obstacles faced by teachers in fostering student character through the school literacy movement. This research uses a qualitative method by taking a descriptive approach. The research instrument in this study is the researcher himself by observing, asking, listening, asking and taking research data using a cellphone as a tool to record all conversations, pictures as real evidence, and a notebook that serves to record conversations with data sources or informants. The data collection techniques used are interviews, observation, and documentation. The results of the research and discussion concluded that: first, a very important aspect in fostering students' character through the school literacy movement is by providing students with reading materials containing ethical values, local, national and global wisdom, which are delivered according to the development of students, direct practice in the environment, Implementation of monitoring and evaluation of GLS (School Literacy Movement) activities using indicators of the achievement of each stage. Second, the obstacles faced include some elements in the school that are not ready to participate in literacy activities carried out to realize literacy activities, the cooperation and participation of every element in the school is important to realize quality school literacy activities. Third, the obstacles faced by teachers are at the habituation stage, development, Teachers do not understand the purpose and objectives of the School Literacy Movement, Students are difficult to manage, the room is not large enough, the library schedule, the library is not large enough, and there are not many books.